2020
DOI: 10.1002/jts.22561
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sexual Trauma and Sexual Relationship Power Among Latina Immigrant Farmworkers: The Moderating Role of Gender Norms

Abstract: Sexual trauma is a national public health concern due to the alarming rates at which it occurs and decades of research supporting its long-term deleterious effects on health outcomes. We assessed the impact of gender norms and sexual trauma on power within sexual relationships among Latina immigrant farmworkers. At baseline, participants (N = 175) completed a survey examining demographic information, sexual trauma history, and gender norms; a follow-up was administered 6 months later. Past sexual trauma was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…A 2-factor solution was obtained, machismo and caballerismo. To increase the Cronbach's alpha, question items with less than .30 correlation were removed (MCS items 12,13,15,16,19,20). Cronbach's alpha of the current study is .68.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A 2-factor solution was obtained, machismo and caballerismo. To increase the Cronbach's alpha, question items with less than .30 correlation were removed (MCS items 12,13,15,16,19,20). Cronbach's alpha of the current study is .68.…”
Section: Methodsmentioning
confidence: 99%
“…The cultural value of marianismo assumes women to be naive, submissive, nurturing, selfless, self-sacrificing, family-centered, chaste, and sexually pure. 10 , 19 Female virginity is emphasized. The submissive nature of marianismo perpetuates inhibition of expression and poor direct communication about sex protection between partners 11 which puts women at high sexual risks.…”
Section: Factors Associated With Protected Sexmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, literature on trauma among Latinas focuses primarily on intimate partner violence (Moreno, 2007;Serrata et al, 2020;Silva-Martínez, 2016), sexual assault (Serrata et al, 2020), sexual trauma (Fava et al, 2020), and domestic violence (Edelson et al, 2007) within the immigrant population (Fava et al, 2020;Silva-Martínez, 2016). In a comparative study of Latinas and non-Latinas who survived domestic abuse, Edelson et al (2007) found that Latinas significantly reported more symptoms of depression and lower self-esteem and were more impacted by the trauma as evidenced by unpleasant thoughts or images.…”
Section: The Intersection Of Trauma Gender Ethnicity and Leadershipmentioning
confidence: 99%